North Atlantic killer whale Orcinus orca populations: a review of current knowledge and threats to conservation. (12th September 2019) - Jourdain, Eve; Ugarte, Fernando; Víkingsson, Gísli A.; Samarra, Filipa I. P.; Ferguson, Steven H.; Lawson, Jack; Vongraven, Dag; Desportes, Geneviève
Abstract: The first comprehensive review on North Atlantic killer whales Orcinus orca was published in 1988. Since then, a significant increase in published studies has substantially improved our understanding of occurrence patterns, major food sources, abundance and population structuring in the North‐east Atlantic. Dedicated studies on killer whales in the Mid‐ and West Atlantic were undertaken beginning in 2006, mainly following an increase in their presence due to rapidly changing environmental conditions in the Arctic regions of Canada and Greenland. Compiling 111 scientific articles and reports published from 1957 to date, this review assesses the current state of knowledge of North Atlantic killer whale populations. We reviewed distribution, abundance, movements, genetic structure, acoustics, population parameters, and threats, whilst highlighting the connection among regions from east to west. Our results indicated that, while North Atlantic killer whales should be recovering following the end of the harvest, culling and live captures in the 1980s, new emerging threats including chemical pollution, anthropogenic noise and increasing unregulated subsistence harvest in Greenland could be hampering this rebound. There is an urgent need to collect data on the abundance and population structure of killer whales in Greenland and Eastern Canada. A lack of information across most regions of the North Atlantic Ocean has prevented regional status assessments from being conducted. Ongoing and future studies should be aimed at collecting relevant data to undertake these assessments, particularly genetic samples and photo‐identification.